Tinjauan Hukum Eksistensi Dari Undang-Undang Nomor 8 Tahun 2015 Setelah 25 Kali Pengujian Undangundang Di Mahkamah Konstitusi Pada Tahun 2015 - Rajab, Achmadudin (Jurnal Hukum & Pembangunan, 2016)
Direct regional election is the method chosen by the majority of Indonesian to percieve the phrase “democratically elected.” Implementation of simultaneous regional election is governed by Law No. 8 of 2015, which is the amendment of Law No. 1 of 2015. The reason on why the people prefer direct regional election is formation and implication of its legitimacy. Head of local government requires its own legitimacy, so that is why direct election by the people is needed. This is also inline with interpretation of democratic election by the majority of Indonesian people. Moreover, since the first implementation of simultaneous regional election, on 9 Deember 2015, issues and challenges arise. One of the problems is apparent on the emergence of 25 cases of mass judicial review of Law No. 8 of 2015 to the Constitutional Court of the Republic Indonesia. From 25 judicial review cases, 7 of them are granted by the Court.